The immunomodulatory effect of green tea (Camellia sinensis) leaves extract on immunocompromised Wistar rats infected by Candida albicans - Retno Pudji Rahayu, - (Veterinary World, 2018)
Background and Aim: The immunocompromised condition is considered a defect in the immune system. This condition tends to increase the risk of oral candidiasis, due to the inability of the immune system to eliminate the adhesion of Candida albicans and leads to systemic candidiasis with a mortality rate of 60%. Green tea (Camellia sinensis) contains potential antioxidant and immunomodulatory which acts as anticancer, antifungal, and antivirus agent. The aim of this study was to invent herbal-based medicine, which acts as an immunomodulator and antifungal agent to treat fungal infection in immunocompromised patients. Materials and Methods: Thirty-five immunocompromised Wistar rats induced with C. albicans were divided into 7 groups (n=5): Control group (C+); treated for 4 days with green tea extract 1.25% (GT 4), epigallocatechin gallate (EGCG) 1% (EGCG 4), EGC 1% (EGC 4); and treated for 7 days with green tea extract 1.25% (GT 7), EGCG 1% (EGCG 7), and EGC 1% (EGC 7). Tongue tissue was collected and analyzed with immunohistochemistry staining using monoclonal antibody; interleukin (IL)-17A, IL-8, and human beta-defensin 2 (HBD)-2. Data were analyzed using analysis of variance test and Tukey honest significant differences test. Results: The expression of IL-17A, IL-8, and HBD-2 was significantly increased (p=0.000) after green tea extract administration in 7 days, whereas in 7 days, the expression of IL-8, IL-17A, and HBD-2 after EGCG and EGC administration did not give a significant result (p>0.005). Conclusion: Within the limits of this study, green tea extract has the ability as an immunomodulatory agent in an immunocompromised patient infected by C. albicans through expression augmentation of IL-8, IL-17A, and HBD-2 compared to EGCG and EGC.